Comparative genomics of clinical strains of Pseudomonas aeruginosa strains isolated from different geographic sites. Issue 1 (December 2018) - Subedi, Dinesh; Vijay, Ajay; Kohli, Gurjeet; Rice, Scott; Willcox, Mark
Abstract The large and complex genome ofPseudomonas aeruginosa, which consists of significant portions (up to 20%) of transferable genetic elements contributes to the rapid development of antibiotic resistance. The whole genome sequences of 22 strains isolated from eye and cystic fibrosis patients in Australia and India between 1992 and 2007 were used to compare genomic divergence and phylogenetic relationships as well as genes for antibiotic resistance and virulence factors. Analysis of the pangenome indicated a large variation in the size of accessory genome amongst 22 stains and the size of the accessory genome correlated with number of genomic islands, insertion sequences and prophages. The strains were diverse in terms of sequence type and dissimilar to that of global epidemicP .aeruginosa clones. Of the eye isolates, 62% clustered together within a single lineage. Indian eye isolates possessed genes associated with resistance to aminoglycoside, beta-lactams, sulphonamide, quaternary ammonium compounds, tetracycline, trimethoprims and chloramphenicols. These genes were, however, absent in Australian isolates regardless of source. Overall, our results provide valuable information for understanding the genomic diversity ofP .aeruginosa isolated from two different infection types and countries.